Razvitie utomlenija i sredstva ego kompensacii v processe trenirovochnoj i sorevnovatel'noj dejatel'nosti sportsmenov v greble akademicheskoj - Kong, X.; Diachenko, A. (Science in Olympic Sport, 2018)
Objective. To examine the means for increasing the level of specific working capacity of rower athletes taking into account the factors that reduce fatigue when it accumulates in the second half of the distance. Methods. Monitoring of competitive activity, ergometry, respiratory gas analysis, biochemical methods. Results. The article presents an integrated approach to diagnosing functional capabilities and specific working capacity of the top rowers of the province of Shandong (China). Particular attention was paid to the control and assessment of specific working capacity of rowers under conditions of latent (compensated) fatigue. The composition of test tasks, the monitoring of the indicators of the cardiorespiratory system response and energy supply during the periods of steady state (at the initial point of reaching .VO2max) and compensation for fatigue, and after "refusal to continue exercising», and the interpretation of the results of the control made it possible to determine the nature of the functional bases of specific working capacity and also individual parameters of duration and intensity of the training modes. On this basis, new means of specific physical preparation have been developed, which take into account the patterns of fatigue accumulation and the capabilities to compensate for it during the competitive event. A fundamentally important condition for assessing functional capabilities is the identification of the individual load parameters in terms of power, time, and tempo-rhythm structure of work (when working in a boat). Conclusions. It is shown that, in the period of latent fatigue accumulation, in rowers with a high level of specific working capacity under conditions of latent (compensated) fatigue, consumption of O2 decreases by no more than 3.0 %, while the RER ( .VCO2· .VO2-1) increases by 1.01 ± 0,02 arb. un., .VE· .VO2-1 increases by 5-6 %, and .VE·CO2-1 increases by 7-9 %. This group of rowers demonstrated also the high values of .VO2max, La, and ergometer power at .VO2max under simulated conditions of the second half section of the race distance. A decrease in these parameters of the cardiorespiratory response and energy supply of work is accompanied by the changes in the structure of the functional bases of rowing and, as a result, by a decrease in specific working capacity under conditions of latent (compensated) fatigue.